Preparation of MgAl2O4 Nanopowder using Combustion Synthesis Method and Its Properties - Nguyen, Ngoc Yen; Chu, Hoang Duc Anh; Bui, Thi Ngoc Mai; Dang, Quoc Khanh; Le, Minh Hai (Old Journal, 2018)
Preparation of a high purity powder is one of the most important steps in producing transparent MgAl2O4 ceramic. Additionally, the particles are required to have nanoscale scale, uniform size and least agglomeration, which make diffusion enhanced at grain boundary during sintering process, promote densification to achieve full dense bulk material. In present work, solution combustion synthesis was carried out to prepare MgAl2O4 nanopowder from magnesium nitrate hydrate (Mg(NO3)2.6H2O) and aluminum nitrate hydrate (Al(NO3)3.9H2O) as oxidizers and urea CH4N2O as a fuel. The obtained products present large agglomerates of nanoscale particles with average size of about 20 nm. Investigation into the influence of the milling processing on deagglomeration efficiency and properties of sintered samples showed that increasing milling time and ball-to-weight ratio led to reduce agglomerate size and fraction, consequently, enhanced significantly shrinkage value, relative density and compressive strength of sintered MgAl2O4 samples. The relative density and the compressive strength achieved highest values of 98% and 155 MPa, respectively, regarding to the powder with milling condition of 48h milling time and 30/1 ball-to-powder ratio.